AN EVALUATION ON TWO SAHABATKU INDONESIA COURSEBOOKS IN LITTLEJOHN’S TEXTBOOK ANALYSIS FRAMEWORK - Aulia Salsabilla; Shohihuzzihni Shohihuzzihni; Hana Farida (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
The use of proper learning materials in foreign language learning have a pivotal role. Feasibility analysis on language learning material surely different from other subjects’. Sahabatku Indonesia coursebooks has been main reference for BIPA learning programs. This qualitative descriptive research evaluates Sahabatku Indonesia BIPA 3 and Sahabatku Indonesia untuk Pelajar BIPA 3 using Andrew Littlejohn's Textbook Analysis Framework in three steps of analysis. The result of the evaluation shows both coursebooks could accommodate in process of learning BIPA relatively effective. It appears from the linguistic aspect and cultural context in the coursebooks provided comprehensively. Nonetheless, the learning methods still can be improved to make more room for the learners to be more engaged in the language through more active roles in bringing or producing their related texts can still be improved. Keywords: foreign language, learning materials, Indonesian language learning materials, evaluation.